Age-Dependent Reductions in the Level of Glial Fibrillary Acidic Protein in the Prefrontal Cortex in Major Depression - Si, Xiaohong; Miguel-Hidalgo, Jose Javier; O'Dwyer, Gillian; Stockmeier, Craig A; Rajkowska, Grazyna (Neuropsychopharmacology (New York, N.Y.), 2004)
The density of glial cells is reduced in certain layers of the dorsolateral prefrontal cortex in major depressive disorder (MDD). Moreover, there are reductions in the packing density of glial fibrillary acidic protein (GFAP) immunoreactive astrocytes in the same cortical layers in younger subjects with MDD. The objective of the present study was to test if the level of GFAP is preferentially decreased in younger subjects with MDD, and whether GFAP levels are correlated with the age of onset of depression. Post-mortem brain tissue punches from dorsolateral prefrontal cortex were collected from 15 subjects with MDD and 15 age-matched psychiatrically normal control subjects. Western blots were performed on gels containing duplicated samples from both subjects of each matched pair, and on gels containing samples at different ages from either the MDD or the control group. The GFAP level was calculated as the ratio of the optical density of GFAP bands to actin bands in subjects with MDD and nonpsychiatric controls. Levels of GFAP were significantly lower in subjects with MDD as compared to controls and this decrease was most prominent in subjects less than 60 years old at the time of death. In the MDD group, GFAP levels were positively correlated with age at the time of death and show a trend toward correlation with the age of onset of depression. These findings indicate that a decrease in levels of GFAP may contribute to the pathophysiology of MDD, particularly in subjects of relatively young age.